From cellular morphology to molecular and epigenetic anomalies of myelodysplastic syndromes. Issue 7 (18th November 2018) - Gadji, Macoura; Pozzo, Aline Rangel
Abstract : Myelodysplastic syndromes (MDSs) are a myeloid neoplasm with a propensity for natural evolution or transformation to acute leukemias (AL) over time. Mechanisms for MDS transformation to AL remain poorly understood but are related to genomic instability, which affects the production of the different cell lineages. Genomic instability is also generated by dysfunctional telomeres. Indeed telomeres, the protective ends of chromosomes are the backbone of genome stability. Nuclear telomere remodeling is an early indicator of nuclear remodeling preceding the onset of genomic instability and MDS. This review aims to revisit the pathogenesis and pathophysiology of MDS from morphology and cytogenetics to molecular and epigenetic mechanisms. Furthermore, this review will highlight and discuss recent breakthroughs in dysfunctional telomeres and nuclear telomere architecture roles in the pathogenesis and physiopathology of MDS in the global context of genomic instability.